1994
DOI: 10.2466/pms.1994.79.1.448
|View full text |Cite
|
Sign up to set email alerts
|

Test-Retest Reliability of the Dynavision Apparatus

Abstract: The test-retest reliability of two tasks on the Dynavision apparatus was estimated as moderate, with intraclass R correlation coefficients ranging from .71 (for .76 subjects) to .73 (for 41 subjects) and paired correlation coefficients ranging from 75 to 93.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 2 publications
1
31
0
Order By: Relevance
“…[7][8][9] Mean RTs in this study were also comparable with that of Wells et al 7 A preliminary study by Klavora et al 8 recorded and analyzed the number of hits the participants made during all protocols. These protocols were repeated on multiple occasions separated by 2-week intervals, much like our session 3.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…[7][8][9] Mean RTs in this study were also comparable with that of Wells et al 7 A preliminary study by Klavora et al 8 recorded and analyzed the number of hits the participants made during all protocols. These protocols were repeated on multiple occasions separated by 2-week intervals, much like our session 3.…”
Section: Discussionsupporting
confidence: 75%
“…With the shortest between-session duration of 48 hours, Wells et al 7 found intraclass correlation coefficient (ICC) values of .63 to .84 in recreationally active individuals. When separated by 2 weeks, Klavora et al 8 found moderate interclass reliability (.71 and .73) for each of the 2 protocols examined. Yet, an additional study investigated the test-retest reliability of 3 different protocols over a period of 8 weeks found excellent reliability (.88, .92, and .97) for all 3 protocols.…”
mentioning
confidence: 96%
“…Assessment used in research Klavora et al (2000); Klavora, Gaskovski, Heslegrave, Quinn & Young et al (1995a); Klavora, Gaskovski, Martin, Forsyth, Heslegrave, Young & Quinn (1995b); Klavora, Gaskovski & Forsyth (1994).…”
Section: Michon's Levelmentioning
confidence: 99%
“…Among them, the Dynavision TM , which shares some operational characteristics with the VISION COACH, has also been used by rehabilitation and human performance centers for occupational therapy and sport-related training (Klavora et al, 1994). In contrast to the VISION COACH, the main performance metric of Dynavision is the number of "hits" a participant can achieve on various Dynavision tasks (Klavora et al, 1995). Research has examined the test-retest reliability of the Dynavision tasks (Klavora et al, 1994(Klavora et al, , 1995 and investigated the relationship between Dynavision performance and various conventional psychomotor tests, such as the simple response time test (Vesia et al, 2008).…”
mentioning
confidence: 99%